The equation shown below is true for which value of x? 5(x + 2) - 3(x - 6) = 7x
Answer
0 (0 оценки)
1
cchen6389 7 months ago
Светило науки - 11 ответа - 0 помощи

Answer:

x= 28/5 or 5.6

Step-by-step explanation:

5(x+2)−3(x−6)=7x

5(x+2)−3(x−6)=7x

Simplify both sides of the equation.

5(x+2)−3(x−6)=7x

(5)(x)+(5)(2)+(−3)(x)+(−3)(−6)=7x <--(Distribute)

5x+10+−3x+18=7x

(5x+−3x)+(10+18)=7x  <--(Combine Like Terms)

2x+28=7x

2x+28=7x

Subtract 7x from both sides.

2x+28−7x=7x−7x

−5x+28=0

Subtract 28 from both sides.

−5x+28−28=0−28

−5x=−28

Divide both sides by -5.

     

x= 28/5

Answer:

x= 28/5

or

5.6

hope this helps!

Still have questions?